Localization of DNA methyltransferase-1 during oocyte differentiation, in vitro maturation and early embryonic development in cow - Lodde, V. (PAGEPress Publications, 2009)
DNA methyltransferase-1 (Dnmt1) is involved in the maintenance of DNA methylation patterns and is crucial for normal mammalian development. The aim of the present study was to assess the localization of Dnmt1 in cow, during the latest phases of oocyte differentiation and during the early stages of segmentation. Dnmt1 expression and localization were assessed in oocytes according to the chromatin configuration, which in turn provides an important epigenetic mechanism for the control of global gene expression and represents a morphological marker of oocyte differentiation. We found that the initial chromatin condensation was accompanied by a slight increase in the level of global DNA methylation, as assessed by 5-methyl-cytosine immunostaining followed by laser scanning confocal microscopy analysis (LSCM). RT-PCR confirmed the presence of Dnmt1 transcripts throughout this phase of oocyte differentiation. Analogously, Dnmt1 immunodetection and LSCM indicated that the protein was always present and localized in the cytoplasm, regardless the chromatin configuration and the level of global DNA methylation. Moreover, our data indicate that while Dnmt1 is retained in the cytoplasm in metaphase II stage oocytes and zygotes, it enters the nuclei of 8–16 cell stage embryos. As suggested in mouse, the functional meaning of the presence of Dnmt1 in the bovine embryo nuclei could be the maintainement of the methylation pattern of imprinted genes. In conclusion, the present work provides useful elements for the study of Dnmt1 function during the late stage of oocyte differentiation, maturation and early embryonic development in mammals.